El rostro del traductor al español del Orlando innamorato: Francisco Garrido de Villena (ENTHYMEMA, 2017)
This article aims at gathering as much information as possible available on F. Garrido de Villena, who translated Orlando innamorato into Spanish. To this purpose, the text and paratext of his works have been surveyed at length, as well as the news and writings of some of his contemporaries with whom he established a personal or a literary relationship. By doing so, the article locates Garrido de Villena’s figure within the literary, geographical and sociopolitical context in which he lived.
Keywords: Literary Translation; Garrido de Villena; Orlando innamorato; Valencia; 16th Century